2012
DOI: 10.1021/jo3021055
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tetrasubstituted Cyclopentadienes via Palladium-Catalyzed Reaction of (Z)-2-En-4-yn Acetates and N-Methyl Indoles

Abstract: An efficient approach for the synthesis of tetrasubstituted cyclopentadienes through Pd-catalyzed reactions of (Z)-2-en-4-yn acetates with substituted indoles was developed. This methodology has the advantages of broad scope, simple conditions and easily accessible starting materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…demonstrated that this PdCl 2 ‐catalyzed reaction proceeded by a Nazarov‐type 4π‐electrocyclization like in the case of Lee and Toste (Scheme F, bottom) . This work expanded the scope to indole‐substituted Cps and also some notable halogen‐substituted Cps (Scheme F, top) …”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…demonstrated that this PdCl 2 ‐catalyzed reaction proceeded by a Nazarov‐type 4π‐electrocyclization like in the case of Lee and Toste (Scheme F, bottom) . This work expanded the scope to indole‐substituted Cps and also some notable halogen‐substituted Cps (Scheme F, top) …”
Section: Discussionmentioning
confidence: 66%
“…[11a] This work expanded the scope to indole-substituted Cps and also some notable halogen-substituted Cps (Scheme 3F,top). [13] As already mentioned, Nazarov cyclizations represent av ersatile class of reactions that can been used to prepare substituted Cps. In 2010, Liu andc o-workersr eported the formation of multifunctional Cps in at wo-step one-pot reaction from divinyl ketones (Scheme 4A).…”
Section: Introductionmentioning
confidence: 99%
“…Investigating the reaction mechanism, reaction of indoles with ( Z )‐2‐en‐4‐yn acetates 602 in the absence of Pd‐catalyst resulted the indole‐tethered enynes 603 which further underwent cycloisomerization in the presence of Pd‐catalyst (Scheme 152). [174] …”
Section: Metamorphosis Of Heteroarene‐tethered Enynesmentioning
confidence: 99%
“…Investigating the reactionm echanism, reactiono fi ndoles with (Z)-2-en-4-yn acetates 602 in the absence of Pd-catalyst resulted the indoletethered enynes 603 which further underwent cycloisomerization in the presence of Pd-catalyst (Scheme 152). [174] Till date severalc yclization reactions of 2-(2-enynyl)pyridines has been reported for the synthesis of indolizines.I n2 015, Jia and co-workerse xplored Cu-catalyzed synthesis of indolizines 606 incorporated with an external nucleophilic segment in the presenceo fa ne xternal nucleophile.Awide variety of nucleo-philes including 1,3-dicarbonyl compounds, indoles, amides,a lcohol, and water,w ere used in these transformations (Scheme153). The authors postulated two mechanistics cenarios.…”
Section: Metamorphosis Of Heteroarene-tethered Enynesmentioning
confidence: 99%
“…As a result, there is no straightforward method for the functionalisation of Cps. [15][16][17][18][19][20][21][22][23][24] Although the synthesis of various Cps remains challenging, considerable efforts were devoted towards the functionalised Cps, [1,[25][26][27][28][29][30][31][32][33][34][35][36] particularly by 4π-electrocyclisation. [27,28] Substituted Cps can also be formed directly by nickel catalysed [3 + 2] cycloaddition reaction.…”
Section: Introductionmentioning
confidence: 99%